THE INFLUENCE OF PROJECT-BASED LEARNING MODELS ON LITERACY ABILITIES AND CLASS IV SCIENCE LEARNING OUTCOMES - Eda, Junaeda; Nurlina, Nurlina; Bancong, Hartono (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2023)
The aim of the study was to analyze the effect of the Project Based Learning Model on scientific literacy skills and science learning outcomes on the concept of energy sources for class IV SDI Hombes Armed, Gowa Regency. This type of research uses desalin Nonequivalent control group desalin. The number of samples in this study were 60 people, consisting of 30 people in the control class and 30 people in the experimental class. The data collection method used was a learning achievement test to measure learning outcomes, scientific literacy questions to measure scientific literacy abilities, and documentation. Data analysis techniques used are descriptive statistical approaches and inferential analysis, and hypothesis testing. The Manova hypothesis test was 0.000 0.05 malcal Ho was rejected in terms of being accepted with the conclusion that there was an influence on the learning model of Project Balsed Learning on copy literacy skills and student learning outcomes in the first place on the learning of IPAl class IV SDI Hombes Alrmed. So it can be concluded that learning using the project-balanced learning model can affect scientific literacy abilities and student learning outcomes in the material for the concept of energy sources class IV SDI Hombes Alrmed.